Female mate preferences on high‐dimensional shape variation for male species recognition traits. (22nd June 2018) - Siepielski, Adam M.; McPeek, Sarah J.; McPeek, Mark A.
Abstract: Females in many animal species must discriminate between conspecific and heterospecific males when choosing mates. Such mating preferences that discriminate against heterospecifics may inadvertently also affect the mating success of conspecific males, particularly those with more extreme phenotypes. From this expectation, we hypothesized that female mate choice should cause Enallagma females (Odonata: Coenagrionidae) to discriminate against conspecific males with more extreme phenotypes of the claspers males use to grasp females while mating – the main feature of species mate recognition in these species. To test this, we compared cerci sizes and shapes between males that were captured while mating with females to males that were captured at the same time but not mating in three Enallagma species. In contrast to our hypothesis, we found only one of forty comparisons of shape variation that was consistent with females discriminating against males with more extreme cerci shapes. Instead, differences in cerci shape between mating and single males suggested that females displayed directional preferences on 1–4 aspects of cerci shape in two of the species in our samples. These results suggest that whereas some directional biases in mating based on cerci shape occur, the intraspecific phenotypic variation in male cerci size and shape is likely not large enough for females to express any significant incidental discrimination among conspecifics with more extreme shapes.